Pengaruh Kombinasi Sport Massage dan Sinar Infrared terhadap Peningkatan Range Of Motion (Rom) Atlet Cidera Frozen Shoulder - Zaki, Egi Muhamad; Komarudin, Komarudin; Firdaus, Ivan Rivan; Pitriani, Pipit (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effect of a combination of sports massage and infrared light to increase range of motion in athletes with frozen shoulder injuries. This study used a Pre- experimental design with a one group pretest-posttest design. The population in this study were UPI Badminton and Volleyball UKM athletes who had frozen shoulder injuries. The sampling technique used total sampling with 12 subjects. The results of this study after being given treatment to the research subject showed that the flexion segment had a value of t = -5.561, extension value t = -3.063, abduction value t = -3.068, adduction value t = -7.181 with a significance value of 0.00 <0.05, if <0.05, it can be concluded that H1 is accepted. The conclusion obtained is that there is a significant effect on the results of the combination of sports massage and infra red on the range of motion of frozen shoulder injury athletes. Kata Kunci : frozen shoulder, infrared, range of motion, dan sport massage